Physiological Activity Among Cocoa Plants Derived from Orthotropic and Plagiotropic Cuttings, Top Grafting, and Hybrid Seed in Drought - Santoso, Teguh Iman; Sulistyaningsih, Endang; Putra, Eka Tarwaca Susila; Susilo, Agung Wahyu (Trends in Sciences, 2025)
Drought is one of the major limiting factors for the growth and development of cocoa. This research aimed to investigate the physiological responses of cocoa plants through novel vegetative propagation methods, namely orthotropic cuttings (OC) and plagiotropic cuttings (PC) under drought stress conditions. These were compared to established propagation methods, including orthotropic grafting (OG), plagiotropic grafting (PG), and hybrid seeds (HS). A complete randomized block design with 2 factors was used in this study, soil water status consisting of well watered (WW) and drought stress (DS), and the propagation method (OC, PC, OG, PG and HS). DS was applied using the fraction of transpirable soil water method. Relative water content, photosynthetic activity, reactive oxygen species, and antioxidant activity were evaluated. The results showed that cocoa plants derived from different propagation methods had varying drought responses. The OC exhibited moderate tolerance to drought, comparable to PG and OG, whereas PC showed the lowest tolerance. Moreover, HS exhibited high tolerance to drought. The OC showed better drought adaptation capability compared to PC, as evidenced by its ability to maintain relative water content, chlorophyll, stomatal conductance and transpiration rate under drought. The OC also exhibited a lower risk of cell damage than others due to a smaller increase in superoxide free radicals and a significant increase in antioxidant activity under drought. These findings indicate that, given its moderate drought tolerance, OC can be recommended as suitable planting material for cacao cultivation in distinctly dry climate regions. HIGHLIGHTS The propagation of cocoa through cuttings offers a promising alternative approach to vegetative reproduction. Evaluation of the physiological activity of cutting-origin cocoa plants under drought and post-drought, especially those derived from orthotropic and plagiotropic shoots, is needed. The physiological adaptation strategies of orthotropic cuttings under drought and post-drought were found to be similar to those of plagiotropic grafted plants, a standard method of vegetative propagation, according to cluster analysis. Plagiotropic cuttings demonstrated distinct physiological adaptation strategies under drought conditions compared to orthotropic cuttings. GRAPHICAL ABSTRACT